Intraperitoneal Fluid Therapy in Children - Harden Noerasid; Pitono Soeparto; Bing Rudyanto; Sugeng Sugijanto; Abdul Hamid; A. Saraswati (Paediatrica Indonesiana, 1975)
The administration of intraperitoneal fluid to 56 children, with gastroenteritis and dehydration, admitted to the Department of Child Health Dr. Soetomo Hospital, was discussed. The authors especially considered the practical aspects and the danger arising from the administration of intraperitoneal fluids. Although none of the patients died, some did show restlessness, meteorism, a raised leucocyte-count and a small rise in body temperature. The authors are of the opinion that the administration of intraperitoneal fluids is not free of danger and it should be reserved for emergency situation only.